2008
DOI: 10.1007/s00436-008-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

The induction of T helper type 1 response by cytokine gene transfection protects mice against secondary hydatidosis

Abstract: Infection of BALB/c mice with protoscoleces of Echinococcus granulosus constitutes a model for the study of secondary hydatidosis (SH) and the associated immune response in immunization and infection trials. This study aimed at testing the efficacy of the cytokine gene expression approach to modulate the immune response and the magnitude of cyst development in mice with secondary hydatidosis. At the time of cyst development (28 days post infection), mice were injected intramuscularly with an expression vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Studies with mouse models to overexpress cytokines by inducing cytokine expression vectors showed that IL-12 and IFN-gamma induce a parasite-specific IgG2a response in mice infected with protoscoleces of E. granulosus whereas in IL-4-gene-transfected mice, IgG1 was elevated, indicating that IgG1 and IgG2 antibody isotypes are regulated by Th1 and Th2 cytokines, respectively [43]. …”
Section: Host Immune Responses To Hydatid Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with mouse models to overexpress cytokines by inducing cytokine expression vectors showed that IL-12 and IFN-gamma induce a parasite-specific IgG2a response in mice infected with protoscoleces of E. granulosus whereas in IL-4-gene-transfected mice, IgG1 was elevated, indicating that IgG1 and IgG2 antibody isotypes are regulated by Th1 and Th2 cytokines, respectively [43]. …”
Section: Host Immune Responses To Hydatid Infectionmentioning
confidence: 99%
“…Mice injected with a vector expressing IL-4 displayed six times higher cyst load than the load in control mice [43], indicating IL-4 plays an important role in hydatid cyst development in the mammalian host.…”
Section: Host Immune Responses To Hydatid Infectionmentioning
confidence: 99%
“…Mice injected with an expression vector encoding IL-12 (20) or treated with rIL-12 (21) were protected against secondary CE and AE, respectively, and this was accompanied by a Th1 response. TLR is believed to play a key role in the innate immune system, but there is limited information on its involvement in innate resistance against Echinococcus infection.…”
Section: Figurementioning
confidence: 99%
“…Mice injected with a vector expressing IL-4 showed higher cyst load than the load in control mice (Al-Qaoud and Abdel-Hafez 2008). So IL-4 may play an important role in hydatid cyst development in the mammalian host (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 93%